Source - Cannon, Geoffrey; Leitzmann, Claus (World Nutrition, 2014)
Geoffrey Cannon  Claus Leitzmann With (top row) Hélène Delisle, Barrie Margetts, Tony McMichael, Barry Popkin, Ricardo Uauy, Mark Wahlqvist Top choices of books, authors, made by public health, nutrition leaders